PEMANTAPAN DIMENSI ETIKA DAN ASAS SEBAGAI PENGUATAN SISTEM HUKUM LINGKUNGAN DI INDONESIA - Himas Muhammady Imammullah El Hakim (Universitas Muhammadiyah Malang, 2021)
Humans as social beings who use the environment make the law an instrument of regulation and protection. Laws relating to the environment itself systemically provide both general and specific regulation. However, environmental law instruments still require further development through strengthening of the ethical dimension. Ethics as one of the norms that can be codified and processed through the judiciary can strengthen the implementation of environmental law. The study was conducted by means of a literature study and analysis in order to find ethical positions and opportunities in the environmental law system. The Job Creation Act which directly changes the politics of environmental law certainly presents its own challenges. This development requires encouragement from other systems, one of which is ethics by presenting a positive ethical system as a law of ethics, both code of ethics and court of ethics. ethical law system that specifically regulates environmental law then requires general principles so that the ethical law instrument can take shape and be applied properly. There are several general principles of environmental law ethics, including the principle of clarity of purpose, the principle of independence, the principle of justice, the principle of certainty, the principle of benefit, the principle of balance, the principle of openness and the principle of protection. The challenge of implementing the general principles of environmental law ethics is in both substantial and formal dimensions that can be encouraged by the holders of power as constitutional mandates in the context of realizing the ideals of the state through the implementation of the mandate of the MPR Decree VI/MPR/2001 concerning the Ethics of the Nation's Life.